Edukasi Sebagai Upaya Pencegahan Kekerasan Seksual Pada Anak di SDN 1 Tataaran 1 - Deviana Munthe; Bintang Sri Rejeki Panjaitan; Grace L.D. Lingga (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
Abstract Comprehensive sexuality education has an important role in equipping the young generation to live a safe and productive life. This education is a form of learning that helps children understand and manage problems related to sexual urges. This community service activity was carried out to provide an understanding of sexual education to students in grades IV, V, and VI at SDN 1 Tataaran 1, South Tondano District, Minahasa Regency, North Sulawesi, with a total of 45 participants. The implementation method includes lectures, discussions, and questions and answers supported by educational video media through laptops and LCD. The results of the activity showed a positive response from both teachers and students, which was reflected in the enthusiasm of students in participating in the entire series of counseling. Based on the evaluation, it was found that there was an increase in students' knowledge about reproductive health and sexuality, shown through the ability of participants to answer post-activity questions. Through this program, it is hoped that children will be better prepared to face sexual changes in themselves and be able to maintain optimal body health. Keywords: Socialization; prevention; sexual violence, children, early childhood